Powstania śląskie w literaturze niemieckiej i polskiej. Pamięć – czas – historia (PDF 450 KB) (Książnica Śląska, 2025)
The author analyses the subject of the Silesian Uprisings both in Polishand German writing. She draws our attention to the function of collective memory and the experience of story telling and recollectingas well as she mentions the most significant theoretical works (e.g.Reinhart Koselleck’s Historical Semantics and Sediments of Time)which focus on time-history relationship. The concept of „sedimentsof time” enables us to perceive the Silesian events of 1919–1921from an utterly new perspective. Memory and culture of the memory, which tend to replace the history itself, contribute to search ofnew testimonies and revision of previous messages. These processesenable us to observe extensively not only the subject of the SilesianUprisings in Polish and German writing but also variations of historical changes within three sediments of time.